A felvidéki akció : állami gazdaságpolitika a peremvidékek felzárkóztatása érdekében - Nagy, Mariann (Közép-Európai Közlemények, 2009)
At the beginning of the dualist era (1867) all the leading politicians and economic experts of Hungary were for free trade and competition, for economic liberalism. But by the end of the 19th century they gradually moved towards the view that the state should intervene to the economy in order to reach a more balanced development of regions and branches of economy. Our paper presents three interventions of the state at the end of the 19th and at the beginning of the 20th century.